Malawi Africa Research in Sustainable Intensification for the Next Generation (Africa RISING) Follow-up Survey - International Food Policy Research Institute (International Food Policy Research Institute, 2023)
Malawi Africa RISING follow-up evaluation survey was implemented in 2019. The survey data were collected from the same households that were interviewed as part of the Malawi baseline evaluation survey. Please refer to "A user guide to Malawi Africa Research in Sustainable Intensification for the Next Generation (Africa RISING) Baseline Evaluation Survey" data paper for details about survey coverage and design. The Malawi follow-up survey was implemented using structured questionnaires that were highly comparable with the questionnaires used in the Mali baseline evaluation survey.